Transient Analysis Of An Optimized Robust Controller In A Hydraulic System - Ghazali, Rozaimi; Chong, Chee Soon; Chai, Mau Shern; Md. Sam, Yahaya; Has, Zulfatman (Asian Research Publishing Network, 2021)
An electro-hydraulic actuator (EHA) system is a prevalent mechanism in industrial sectors that required high force such as steel, automotive and aerospace industries. It is a challenging task to acquire precision when dealing with a system that can produce high force. Besides, since most of the mechanical actuator performance varies with time, it is even difficult to ensure its robustness characteristic towards time. Therefore, this paper proposed the industrial’s well-known controller, which is the proportional-integral-derivative (PID) controller that can improve the precision and the robustness or the EHA system. Then, an enhanced PID controller, which is the fractional order PID (FOPID) controller will be applied. Both controllers are optimized using particle swarm optimization (PSO) algorithm. Then, this paper will focus to analyse the transient response performance of both controllers through the step and multiple-step response. As a result, it is observed that the precision and robustness characteristic of the FOPID is greater than the PID controller.